Winning the future - a business overview - Nellis, Joseph G. (Institute of Chartered Accountants in England & Wales (ICAEW), 2007)
In his recent lecture to the Finance & Management Faculty, Joe Nellis identified which would be the winning business sectors of the future. Here he summarises his arguments.